Determinants of Deescalation Failure in Critically Ill Patients with Sepsis: A Prospective Cohort Study. (14th July 2016) - Salahuddin, Nawal; Amer, Lama; Joseph, Mini; El Hazmi, Alya; Hawa, Hassan; Maghrabi, Khalid
Abstract : Introduction . Deescalation refers to either discontinuation or a step-down of antimicrobials. Despite strong recommendations in the Surviving Sepsis Guidelines (2012) to deescalate, actual practices can vary. Our objective was to identify variables that are associated with deescalation failure. Methods . In this prospective study of patients with sepsis/septic shock, patients were categorized into 4 groups based on antibiotic administration: no change in antibiotics, deescalation, escalation (where antibiotics were changed to those with a broader spectrum of antimicrobial coverage), or mixed changes (where both escalation to a broader spectrum of coverage and discontinuation of antibiotics were carried out). Results . 395 patients were studied; mean APACHE II score was24 ± 7.8 . Antimicrobial deescalation occurred in 189 (48%) patients; no changes were made in 156 (39%) patients. On multivariate regression analysis, failure to deescalate was significantly predicted by hematologic malignancy OR 3.3 (95% CI 1.4–7.4)p < 0.004, fungal sepsis OR 2.7 (95% CI 1.2–5.8)p = 0.011, multidrug resistance OR 2.9 (95% CI 1.4–6.0)p = 0.003, baseline serum procalcitonin OR 1.01 (95% CI 1.003–1.016)p = 0.002, and SAPS II scores OR 1.01 (95% CI 1.004–1.02)p = 0.006 . Conclusions . Current deescalation practices reflect physician reluctance when dealing with complicated, sicker patients or with drug-resistance or fungal sepsis. Integrating an antibiotic stewardship program may increase physician confidence and provide support towards increasing deescalation rates.